Development of portable energy sources based on hydrogen fuel cell with regeneration - B. V. Malozyomov; E. G. Porsev; Б. В. Малозёмов; Е. Г. Порсев (Международный издательский дом научной периодики "Спейс, 2024)
The paper was the first to analyze the possibility of using small fuel cells to power automation devices, analyze their disadvantages and advantages, and their demand in modern electric power industry, taking into account the processes characteristic of low-voltage control circuits. The possibilities of using an economical current source as a current source for emergency power supply of automated control system devices are considered, which can create an effective commercial basis for the implementation of this solution in an industrial production area in conditions of possible power outages (Far North, Far East, conditions of remoteness of the central power supply), An analysis of the areas of application of fuel cells was carried out. The technical characteristics of elements for powering automation devices have been determined, and chemical and electrical calculations of the fuel cell under study have been carried out. В работе впервые проведён анализ возможности применения малых топливных элементов для питания устройств автоматики, проанализированы их недостатки и преимущества, востребованности в современной электроэнергетике с учётом процессов характерных для низковольтных цепей управления. Рассмотрены возможности применения экономичного источника тока, как источника тока для аварийного питания приборов АСУТП, который может позволить создать эффективную коммерческую основу для внедрения данного решения в зону промышленного производства в условиях возможных перебоев в электроснабжении (Крайний Север, Дальний Восток, условия удалённости центрального энергоснабжения), проведен анализ областей применения топливных элементов. Определены технические характеристики элементов для питания устройств автоматики, проведен химический и электрический расчёт исследуемого топливного элемента.